Midwifery practice: Concept Paper - Tshuma, Bongani; Kasu, Christine, Mary; Mugadza, Gladys (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Objectives: Midwifery practice is often not well understood. Midwifery practice is dynamic and varies in many countries. It ranges from preconception care, care given to women during pregnancy, labour and delivery, and postpartum care to competencies expected of individual practice. The objective of this paper was to clarify, explain and describe the concept of Midwifery Practice. Methods: The concept analysis of Midwifery Practice was done using the eight steps of Walker and Avant’s strategic method. Initially twenty-five (25) articles from year 2000 to 2017 were reviewed. Six (6) articles were later dropped due to their irrelevant information, and nineteen (19) articles were finally reviewed to describe Midwifery Practice. Results: The main antecedents of Midwifery Practice were a Diploma in General Nursing and enrolment into a post-basic Diploma in Midwifery for one year. On successful completion of the midwifery course, he/she registers with the nurse’s council to practice as a midwife. The attributes identified in literature for Midwifery Practice include the requisite knowledge in midwifery, performance of the expected competencies, and having the authority to practice as a midwife. The resultant consequences of Midwifery Practice include support, care and advice given to women during pregnancy, labour and post-partum period, and the care of the newborn. They also include reduction in maternal and neonatal morbidity and mortality, and job satisfaction. The empirical referents fundamental to Midwifery Practice include ability to take complete history and perform a physical examination to diagnose risk factors, manage and refer appropriately. They also include conducting clean and safe deliveries, and management of obstetric emergencies. Conclusion: Midwifery Practice may take several forms but should be in line with international standards as described by the International Confederation of Midwives. In view of the important role played by midwives in the health delivery system, it is crucial for each practitioner to understand the scope of their practice. The midwife is recognised as a responsible and accountable professional who works with and in partnership with women to give the necessary support, care and advice during pregnancy, labour and the post-partum period.